Solar cell and method of manufacturing the same, multi-junction solar cell, photovoltaic module, power generation device, and electric device

CN122995393APending Publication Date: 2026-10-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510523282.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]然而,相关技术中钙钛矿太阳能电池的稳定性差,光电性能低,阻碍了其实际应用和产业化发展

Benefits of technology

[0035]本申请第四方面还提供一种发电装置,所述发电装置包括本申请第一方面所述的太阳能电池,第二方面所述的多结太阳能电池或根据本申请第三方面所述的制备方法制得的太阳能电池。因此,至少具有上述太阳能电池的优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995393A_ABST
    Figure CN122995393A_ABST
Patent Text Reader

Abstract

The application provides a solar cell and a preparation method thereof, a multi-junction solar cell, a photovoltaic module, a power generation device and a power utilization device. The solar cell comprises a first perovskite material, the first peroviskite material comprises a compound with a chemical formula of [A][B][X]3, wherein A is (H2N-CH=NH2) + ; B is selected from one or more of Pb 2+ , Sn 2+ ; X is I ‑ ; in an X-ray diffraction pattern of the compound, the peak area ratio of the (111) crystal face to the sum of the peak areas of the (111) crystal face and the (001) crystal face is 80% to 100%, and the difference between the band gap of the compound and a reference band gap is less than or equal to 0.05 eV, wherein the reference band gap is the band gap of the uncontrolled [A][B][X]3 peroviskite measured by ultraviolet-visible spectroscopy in a state of maintaining a stable cubic crystal phase. The solar cell has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a solar cell and its preparation method, a multi-junction solar cell, a photovoltaic module, a power generation device, and an electrical device. Background Technology

[0002] In recent years, global energy shortages and environmental pollution have become increasingly prominent, leading to growing attention on solar cells as an ideal renewable energy source. Solar cells, also known as photovoltaic cells, are devices that directly convert light energy into electrical energy through the photoelectric effect or photochemical effect.

[0003] Perovskite solar cells (PSCs) are solar cells that utilize perovskite materials as light-absorbing materials. Compared with other solar cells, perovskite solar cells stand out in the field of solar cells due to their advantages such as low cost, high efficiency, and simple manufacturing process.

[0004] However, the poor stability and low photoelectric performance of perovskite solar cells in related technologies hinder their practical application and industrialization. Therefore, improving the photoelectric performance of perovskite solar cells remains an urgent technical problem to be solved. Summary of the Invention

[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a solar cell and a method for preparing the same, a multi-junction solar cell, a photovoltaic module, a power generation device, and a power consumption device. The solar cell exhibits good stability and photoelectric conversion efficiency.

[0006] The first aspect of this application provides a solar cell, the solar cell including a first light-absorbing layer, the first light-absorbing layer including a first perovskite material, the first perovskite material including a compound of formula (1), [A][B][X]3(1);

[0007] In the formula, A is (H2N-CH=NH2). + B is selected from Pb 2+ Sn 2+ One or more of them; X is I -In the X-ray diffraction pattern of the compound of formula (1), the peak area of ​​the (111) crystal plane accounts for 80% to 100% of the sum of the peak areas of the (111) and (001) crystal planes. The difference between the band gap of the compound of formula (1) and the reference band gap is less than or equal to 0.05 eV. The reference band gap is the band gap measured by UV-Vis spectroscopy of the uncontrolled [A][B][X]3 perovskite in a stable cubic crystal phase. Thus, in the compound of formula (1), the (111) crystal plane is arranged as the dominant crystal plane, which is beneficial to releasing the lattice stress caused by the large formamidinium ions, so that the compound of formula (1) can remain stable at room temperature. In addition, the band gap of the first perovskite material is closer to its corresponding reference band gap, which is beneficial to the first perovskite material to maintain a higher theoretical device limit efficiency while improving stability, and is beneficial to the solar cell to have good stability and photoelectric conversion efficiency.

[0008] In some embodiments, in the X-ray diffraction pattern of the compound of formula (1), the peak area of ​​the (111) crystal plane accounts for 95%-97% of the sum of the peak areas of the (111) crystal plane and the (001) crystal plane. This is beneficial to improving the stability of the solar cell.

[0009] In some embodiments, the crystal structure of the compound of formula (1) belongs to the cubic crystal system, wherein the residual lattice stress of the compound of formula (1) is 0.1 MPa-4.0 MPa. Therefore, the lattice stress generated by the larger formamidinium ion at site A in the compound of formula (1) is relatively small, which is beneficial to improving the stability of the solar cell.

[0010] In some embodiments, the first light-absorbing layer further includes a compound represented by formula (2).

[0011]

[0012] In the formula, R1 is selected from H and C1-C3 alkyl groups, and R2 and R3 are each independently selected from H, branched or straight-chain C1-C4 alkyl groups, and R2 and R3 are not both hydrogen. The compound represented by formula (2) is located in the grain boundaries of the first perovskite material. This is beneficial for reducing nonradiative recombination of charge carriers and improving the performance of solar cells.

[0013] In some embodiments, the content of the compound represented by formula (2) is 0.01% to 0.5% relative to the total mass of the first light-absorbing layer. This is beneficial to improving the passivation effect of the first perovskite material and enhancing the performance of the solar cell.

[0014] In some embodiments, the solar cell further includes a first electrode and a second electrode, wherein the first light-absorbing layer is disposed between the first electrode and the second electrode.

[0015] In some embodiments, the solar cell further includes a first carrier transport layer disposed between the first electrode and the first light-absorbing layer, and / or a second carrier transport layer disposed between the second electrode and the first light-absorbing layer; wherein the first carrier transport layer is selected from either a hole transport layer or an electron transport layer, and the second carrier transport layer is selected from either either a hole transport layer or an electron transport layer. This enhances the extraction and transport of electrons and holes, thereby contributing to improved photoelectric conversion efficiency of the solar cell.

[0016] In some embodiments, the solar cell further includes a second light-absorbing layer disposed between the first electrode and the second electrode, wherein the first light-absorbing layer and the second light-absorbing layer have different band gaps. Thus, by providing a first light-absorbing layer and a second light-absorbing layer with different band gaps, the solar cell can effectively absorb light of different wavelengths, broadening the spectral range of light absorbed by the solar cell and improving the photoelectric conversion efficiency of the solar cell.

[0017] In some embodiments, the second light-absorbing layer comprises a layer of the following compounds: a second perovskite material, crystalline silicon, copper zinc tin sulfide, copper zinc tin selenide, copper zinc tin selenide sulfide, copper indium gallium selenide, copper indium gallium diselenide, or copper indium selenide.

[0018] In some embodiments, the solar cell includes a first electrode, an optional first carrier transport layer, a first light-absorbing layer, an optional second carrier transport layer, a composite layer, an optional third carrier transport layer, the second light-absorbing layer, an optional fourth carrier transport layer, and a second electrode, all stacked together. The first carrier transport layer is selected from either a hole transport layer or an electron transport layer, the second carrier transport layer is selected from either a hole transport layer or an electron transport layer, the third carrier transport layer has the same carrier transport performance as the first carrier transport layer, and the fourth carrier transport layer has the same carrier transport performance as the second carrier transport layer. Thus, the arrangement of the carrier transport layers helps to extract and transport electrons or holes generated by the first or second light-absorbing layer, enhancing the extraction and transport effect of electrons and holes and improving the performance of the solar cell.

[0019] A second aspect of this application also provides a multi-junction solar cell, the multi-junction solar cell including a first sub-cell disposed on one side of the second sub-cell along the thickness direction, wherein the first sub-cell is the solar cell described in the first aspect of this application. This provides at least the advantages of the aforementioned solar cell.

[0020] In some embodiments, the second sub-cell includes at least a third light-absorbing layer, which includes a third perovskite material, crystalline silicon, copper zinc tin sulfide, copper zinc tin selenide, copper zinc tin selenide sulfide, copper indium gallium selenide, copper indium gallium diselenide, or copper indium selenide.

[0021] In some embodiments, the multi-junction solar cell includes a first electrode, an optional first carrier transport layer, a first light-absorbing layer, an optional second carrier transport layer, a third electrode, an insulating layer, a fourth electrode, an optional fifth carrier transport layer, the third light-absorbing layer, an optional sixth carrier transport layer, and a second electrode, all stacked together. The first carrier transport layer is selected from either a hole transport layer or an electron transport layer; the second carrier transport layer is selected from either a hole transport layer or an electron transport layer; the fifth carrier transport layer is selected from either a hole transport layer or an electron transport layer; and the sixth carrier transport layer is selected from either a hole transport layer or an electron transport layer.

[0022] This application also provides a method for fabricating a solar cell, including forming a first light-absorbing layer, wherein forming the first light-absorbing layer includes the following steps:

[0023] Preparation of perovskite precursor solution: Dissolve metal iodide, (H2N-CH=NH2)I, first additive and second additive in solvent and stir to obtain perovskite precursor solution. The metal iodide includes one or both of PbI2 or SnI2. The first additive and second additive together form a volatile compound.

[0024] Preparation of the first light-absorbing layer: The perovskite precursor solution is coated onto the substrate and then heat-treated to form the first light-absorbing layer. This helps to improve the stability of the solar cell.

[0025] In some embodiments, during the step of preparing the perovskite precursor solution, the molar percentage of the first additive or the second additive is 1 mol% to 10 mol% relative to the molar amount of the metal iodide. This is beneficial for improving the stability of the solar cell.

[0026] In some embodiments, the first additive is R1-CO-NH2, and the second additive is an organic amine salt, wherein the organic amine salt corresponds to an organic amine with the structural formula R2-NH-R3, where R1 is selected from H or C1-C3 alkyl groups, and R2 and R3 are each independently selected from H, branched or straight-chain C1-C4 alkyl groups, and R2 and R3 are not both hydrogen. This is beneficial for improving the stability of solar cells.

[0027] In some embodiments, the preparation method satisfies one or more of the following:

[0028] (1) The first additive is selected from one or more of formamide, acetamide, propionamide, and 2-methylpropionamide;

[0029] (2) The salt corresponding to the organic amine salt is selected from one or more of hydrochloride, bromate, iodate, acetate, and sulfate;

[0030] (3) The organic amine salt corresponds to one or more of the following cations: dimethylamine cation, diethylamine cation, di-n-propylamine cation, diisopropylamine cation, di-n-butylamine cation, and diisobutylamine cation. This is beneficial for improving the stability of the solar cell.

[0031] In some embodiments, the molar ratio of the first additive to the second additive is 1 to 1.2:1. This is beneficial for improving the stability of the solar cell.

[0032] In some embodiments, the molar concentrations of the metal iodide and (H₂N-CH=NH₂)I in the perovskite precursor solution are each independently 1-2 mol / L. This is beneficial for improving the stability of the solar cell.

[0033] In some embodiments, the heat treatment in the step of preparing the perovskite layer includes annealing at 80-120°C for 8-20 minutes. This is beneficial for improving the stability of the solar cell.

[0034] A third aspect of this application also provides a photovoltaic module, which includes the solar cell described in the first aspect of this application, the multi-junction solar cell described in the second aspect, or a solar cell prepared according to the preparation method described in the third aspect of this application. Therefore, it possesses at least the advantages of the aforementioned solar cells.

[0035] A fourth aspect of this application also provides a power generation device, which includes the solar cell described in the first aspect of this application, the multi-junction solar cell described in the second aspect, or a solar cell prepared according to the preparation method described in the third aspect of this application. Therefore, it possesses at least the advantages of the aforementioned solar cells.

[0036] A fifth aspect of this application also provides an electrical device comprising the solar cell described in the first aspect of this application, the multi-junction solar cell described in the second aspect, or a solar cell prepared according to the preparation method described in the third aspect of this application. Therefore, it possesses at least the advantages of the aforementioned solar cells. Attached Figure Description

[0037] Figure 1This is a schematic diagram of the structure of a solar cell according to one embodiment of this application.

[0038] Figure 2 This is a schematic diagram of the structure of a solar cell according to another embodiment of this application.

[0039] Figure 3 This is a schematic diagram of the structure of a solar cell according to another embodiment of this application.

[0040] Figure 4 This is a schematic diagram of the structure of a multi-junction solar cell according to an embodiment of this application.

[0041] Figure 5 The XRD patterns are shown for the perovskite materials in the solar cells prepared in Examples 1 and 4 of this application.

[0042] Figure 6 The residual stress diagram is shown for the perovskite material of the solar cell prepared in Example 1 of this application.

[0043] Explanation of reference numerals in the attached figures:

[0044] 10 Solar cell; 11 First electrode; 12 Second electrode; 13 First light-absorbing layer; 141 Hole transport layer; 142 Electron transport layer; 15 Second light-absorbing layer; 200 Multi-junction solar cell; 201 First sub-cell; 202 Second sub-cell Detailed Implementation

[0045] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the solar cell, its fabrication method, photovoltaic module, power generation device, and power consumption device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0046] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0047] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0048] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0049] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be tested using various testing methods commonly used in the art, such as the testing methods provided in this application.

[0050] In this application, the term "electrode" refers to a region or layer composed of or substantially composed of electrode material.

[0051] As used in this application, the term "layer" refers to any substantially layered structure. A layer may have a thickness that varies along its length. Typically, the thickness of a layer is approximately constant. As used in this application, "thickness" refers to the average thickness of the layer. The thickness of a layer can be measured using methods conventional in the art.

[0052] Unless otherwise specified, the term "arranged / set on" means that one component is provided or set on another component. The first component may be provided directly on or placed on the second component, or a third component may be present between the first and second components. For example, if the first layer is set on the second layer, this includes cases where there is an intermediate third layer between the first and second layers.

[0053] As used in this application, the term "perovskite" refers to a material having a three-dimensional crystal structure associated with the three-dimensional crystal structure of CaTiO3, or a layered material comprising a structure associated with the structure of CaTiO3. Materials having a three-dimensional crystal structure associated with CaTiO3 are known and may be referred to as perovskites with a "3D perovskite structure," or simply "3D perovskites." Materials comprising layers of perovskite material are known and are referred to in the art as "2D layered perovskites." When exposed to sunlight, electrons in a perovskite are excited, transitioning from the valence band to the conduction band, generating electron-hole pairs. Unless otherwise specified, "perovskite" in this application refers to 3D perovskite materials. The general chemical formula of perovskite can be represented as ABX3, where A is typically a cation with a larger radius, B is a cation with a smaller radius, and X is an anion. When a perovskite includes more than one type of A cation, the different A cations can be distributed in an ordered or disordered manner at the A sites. When a perovskite includes more than one type of B cation, the different B cations can be distributed in an ordered or disordered manner at the B sites. Similarly, when a perovskite includes more than one type of X anion, the different X anions can be distributed in an ordered or disordered manner at the X sites.

[0054] Solar cells, also known as photovoltaic cells, are devices that directly convert light energy into electrical energy through the photoelectric effect or photochemical effect. Perovskite solar cells (PSCs) are solar cells that utilize perovskite material as the light-absorbing material. Compared with other solar cells, perovskite solar cells have high photoelectric conversion efficiency. Unless otherwise specified, in the following text, solar cells refer to solar cells whose light-absorbing layer contains perovskite material, and can also be called perovskite solar cells.

[0055] FAPbI3 perovskite materials have attracted widespread attention due to their suitable band gap and excellent intrinsic thermal stability. However, the uncontrolled active phase of FAPbI3 (i.e., pure FAPbI3) suffers from poor stability due to lattice stress caused by the excessively large effective ionic radius of formamidinium ions (FA). At room temperature, it transforms from the active α phase (black) into a transparent inactive phase, making it difficult to apply in solar cells. To stabilize FAPbI3 perovskite materials into an active phase, researchers often employ methods such as doping to construct multi-component formulations, for example, doping MA at the A sites in ABX3 perovskite materials. + Cs + 、Rb + Wait, doping Br at the X site - Cl -Thus, FAPbI3 perovskite materials can maintain a stable active phase under solar operating conditions. However, doping ions usually cause lattice distortion in FAPbI3 perovskite, leading to band gap widening and reducing the theoretical limit efficiency of solar cells. Furthermore, multi-component formulations of FAPbI3 perovskite materials reduce the compositional uniformity of the perovskite film in solar cells, thereby decreasing the overall efficiency and long-term stability of the solar cells. Therefore, a perovskite solar cell with good stability and high photoelectric conversion efficiency is needed. Similarly, FASn... x Pb y I3 perovskite (where 0 ≤ 1, 0 < y < 1, and x + y = 1) can also lead to lattice stress due to the excessively large effective ionic radius of FA, resulting in pure FASn. x Pb y The I3 perovskite crystal phase is unstable.

[0056] In view of this, this application provides a solar cell and its fabrication method, a photovoltaic module, a power generation device, and a power consumption device. The solar cell of this application has good stability and high photoelectric conversion efficiency.

[0057] Solar cells

[0058] Typically, a solar cell comprises a first electrode (the electrode that first receives incident light), a light-absorbing layer, and a second electrode (the electrode that last receives incident light), arranged sequentially along the direction of light incidence. The photoelectric conversion principle of a solar cell is as follows: Incident light (e.g., sunlight) enters the device through the first electrode, then reaches the light-absorbing layer and is absorbed. Under the excitation of the incident light, the light-absorbing layer generates electron-hole pairs. Under the action of an electric field, the holes and electrons separate, with the electrons transported to one electrode and the holes transported to the other electrode. Subsequently, a loop is formed through an external circuit, which can be used to drive a load.

[0059] [First light absorption layer]

[0060] The solar cell of this application includes a first light-absorbing layer, which comprises a first perovskite material. The first perovskite material comprises a compound of formula (1).

[0061] [A][B][X]3(1);

[0062] In the formula, A is (H2N-CH=NH2). + B is selected from Pb 2+ Sn 2+ One or more of them; X is I - ;

[0063] In the X-ray diffraction pattern of the compound of formula (1), the (111) crystal plane accounts for 80% to 100% of the sum of the peak areas of the (111) crystal plane and the (001) crystal plane. The difference between the band gap of the compound of formula (1) and the reference band gap is less than or equal to 0.05 eV. The reference band gap is the band gap width measured by ultraviolet-visible spectroscopy of the uncontrolled [A][B][X]3 perovskite in a stable cubic crystal phase.

[0064] The modified perovskite material of this application includes compounds of formula (1) above, which have suitable band gaps and excellent intrinsic thermal stability, thus showing potential for application in solar cells, especially in single-junction perovskite solar cells. Perovskites with different crystal orientations have different intrinsic stability. In unmodified pure [A][B][X]3 perovskite material, the (001) crystal plane is the dominant crystal plane, that is, in the XRD test results of the material, the peak area of ​​the (001) crystal plane is higher than the sum of the peak areas of all crystal planes. However, this leads to poor environmental stability of the perovskite material and easy crystal phase transformation. In contrast, [A][B][X]3 perovskite material with the (111) crystal plane as the dominant crystal plane has better environmental stability and higher theoretical device limit efficiency. By ensuring that the proportion of the (111) crystal plane in the compound of formula (1) is within the aforementioned range, it is beneficial for the (111) crystal plane to be arranged as the dominant crystal plane in the compound of formula (1), which helps to release the lattice stress caused by the large formamidinium ions, thus enabling the compound of formula (1) to remain stable at room temperature. In this application, no dopant ions are introduced at the A and X sites in the compound of formula (1), which helps to reduce the lattice distortion in the compound of formula (1), resulting in a smaller change in the band gap of the modified perovskite material compared to the reference band gap. By ensuring that the difference between the band gap of the compound of formula (1) and the reference band gap is less than or equal to 0.05 eV, it is indicated that the band gap of the first perovskite material is closer to its corresponding reference band gap, which helps the first perovskite material maintain a higher theoretical device limit efficiency while improving stability, thereby improving the photoelectric conversion efficiency of the solar cell. For example, the difference between the band gap of the compound of formula (1) and the reference band gap can be 0.05 eV, 0.04 eV, 0.03 eV, 0.02 eV, 0.01 eV, 0.005 eV, 0 eV or any two of these values.

[0065] In this application, the ratio of the (111) and (001) crystal planes in the X-ray diffraction pattern of the compound of formula (1) was determined by X-ray diffraction. The diffraction peak of the (111) crystal plane appeared at a diffraction angle of 2θ = 24.5° ± 1.0° in the XRD spectrum, and the diffraction peak of the (001) crystal plane appeared at a diffraction angle of 2θ = 14.0° ± 1.0° in the XRD spectrum. By calculating the integral area of ​​the diffraction peaks corresponding to the (111) and (001) crystal planes in the XRD spectrum, the ratio of the (111) and (001) crystal planes was calculated. For example, in the X-ray diffraction pattern of the compound of formula (1), the proportion of the (111) crystal plane relative to the sum of the peak areas of the (111) and (001) crystal planes can be 80%, 85%, 88%, 90%, 92%, 95%, 96%, 97%, 98%, 99%, 100%, or a value between any two of these values. In some alternative embodiments, the ratio of the (111) and (001) crystal planes in the X-ray diffraction pattern of the compound of formula (1) is 95% to 97%. This further improves the stability of the compound of formula (1) at room temperature.

[0066] In this application, unregulated [A][B][X]3 perovskite refers to [A][B][X]3 perovskite material obtained by directly annealing [A][X] and [B][X]2 as raw materials without adding any other additives or dopants. For example, unregulated FAPbI3 perovskite refers to perovskite in the general formula [A][B][X]3, where A is a formamidinium ion ((H2N-CH=NH2)). + (abbreviated as FA), B is Pb 2+ X is I -This refers to cubic perovskite materials where sites A, B, and X are free of other doped ions. Taking FAPbI3 perovskite as an example, the uncontrolled FAPbI3 perovskite obtained after annealing is cubic in form. It has poor stability at room temperature and easily transforms into a transparent, inactive phase, i.e., hexagonal FAPbI3 perovskite, making it unsuitable for photovoltaic cells. However, it can maintain a stable cubic crystal form at temperatures above 150°C, thus retaining a stable active phase (appearing black). The reference band gap of uncontrolled FAPbI3 perovskite refers to the band gap width measured by UV-Vis spectroscopy when the uncontrolled FAPbI3 perovskite maintains a stable cubic crystal form. Exemplarily, the method for testing the reference bandgap specifically includes the following steps: annealing uncontrolled FAPbI3 perovskite at 150°C for 30 min, then cooling it to room temperature in an inert N2 environment with humidity below 3% RH, and testing it using a UV-Vis spectrophotometer within 1 hour. During the test, the monochromatic light wavelength is set to scan within the range of 300 nm-900 nm, and the test step size is 5 nm. Those skilled in the art will understand that during the reference bandgap testing process, the cubic perovskite material annealed at 150°C, when cooled to room temperature, maintains a relatively stable cubic crystal form within 1 hour. Therefore, the reference bandgap of uncontrolled FAPbI3 perovskite can be rapidly measured at room temperature. In this application, the reference bandgap of uncontrolled FAPbI3 perovskite was measured to be 1.47 eV. For example, uncontrolled FASnI3 perovskite maintains a stable cubic crystal form at temperatures above 100°C. Therefore, its reference band gap is measured using a method similar to that described above, except that the uncontrolled FASnI3 perovskite is annealed at 100°C for 30 min. The reference band gap of the uncontrolled FASnI3 perovskite measured in this application is 1.33 eV. For example, uncontrolled FAPb... 0.5 Sn 0.5 I3 perovskite maintains a stable cubic crystal structure at temperatures above 120°C. Therefore, its reference band gap was measured using a method similar to the one described above, except that the uncontrolled perovskite was annealed at 120°C for 30 min. The uncontrolled FAPb measured in this application... 0.5 Sn 0.5 The reference band gap for I3 perovskite is 1.21 eV.

[0067] In some embodiments, the crystal structure of the compound of formula (1) belongs to the cubic crystal system, and the residual lattice stress of the compound of formula (1) is 0.1 MPa-4 MPa. By keeping the residual lattice stress of the compound of formula (1) within the above range, it is shown that the lattice stress generated by the larger formamidinium ion at the A site in the compound of formula (1) is smaller, thereby improving the stability of the perovskite material. For example, the residual lattice stress of the compound of formula (1) can be 0.1 MPa, 0.5 MPa, 1.0 MPa, 2.0 MPa, 3.0 MPa, 4.0 MPa, or a value between any two of these values.

[0068] In some embodiments, the first light-absorbing layer further includes the compound shown in formula (2).

[0069]

[0070] In the formula, R1 is selected from H and C1-C3 alkyl groups, and R2 and R3 are each independently selected from H, branched or straight-chain C1-C4 alkyl groups, and R2 and R3 are not both hydrogen. The compound shown in formula (2) is located in the grain boundary of the first perovskite material. By including the compound shown in formula (2) in the first light-absorbing layer, the lone pair electrons contained in -C=O, N, etc. in the compound shown in formula (2) can combine with the B-site cations in the first perovskite material, passivate the defects of the first perovskite material, reduce the nonradiative recombination of charge carriers, and improve the performance of the solar cell.

[0071] In some embodiments, the content of the compound shown in formula (2) is 0.01%-0.5% relative to the total mass of the first light-absorbing layer. By keeping the content of the compound shown in formula (2) within the above range, it is beneficial to improve the passivation effect of the first perovskite material and enhance the performance of the solar cell. Exemplarily, the content of the material shown in formula (2) can be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.275%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, or a value between any two of these values. In some alternative embodiments, the content of the compound shown in formula (2) is 0.01%-0.03%. In one alternative embodiment, the content of the compound shown in formula (2) is 0.0275%. This is beneficial for further improving the performance of the solar cell.

[0072] In some embodiments, the solar cell further includes a first electrode and a second electrode, wherein a first light-absorbing layer is disposed between the first electrode and the second electrode.

[0073] The following description, in conjunction with the accompanying drawings, further illustrates various aspects of the perovskite solar cells of this application.

[0074] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell according to one embodiment of this application. Figure 1 As shown, the perovskite solar cell 10 includes: a first electrode 11, a second electrode 12, and a first light-absorbing layer 13 disposed between the first electrode 11 and the second electrode 12.

[0075] In some embodiments, the first electrode 11 serves as the bottom electrode (transparent electrode) and is the first to receive incident light. In this embodiment, the material used for the first electrode 11 may include a transparent conductive material. This application does not particularly limit the transparent conductive material used for the first electrode 11. Exemplary transparent conductive materials include at least one of indium tin oxide (ITO), fluorine-doped tin oxide (FTO), indium-doped zinc oxide (IZO), aluminum-doped zinc oxide (AZO), boron-doped zinc oxide (BZO), antimony-doped tin oxide, indium-doped tungsten oxide (IWO), and graphene.

[0076] This application does not impose any particular limitation on the thickness of the first electrode 11; a thickness commonly used in the art for the first electrode 11 may be adopted. For example, the thickness of the first electrode 11 is 10 nm to 1000 nm.

[0077] In some embodiments, the second electrode 12 serves as the back electrode, and incident light exits the solar cell from the second electrode 12. In this embodiment, the material used for the second electrode 12 may include a conductive material. This application does not particularly limit the conductive material used for the second electrode 12. For example, the conductive material includes one or more of the above-mentioned transparent conductive materials, metals and their alloys, and elemental carbon materials. Exemplary examples include one or more of gold (Au), silver (Ag), copper (Cu), aluminum (Al), nickel (Ni), chromium (Cr), bismuth (Bi), platinum (Pt), magnesium (Mg), molybdenum (Mo), tungsten (W), and their alloys. Exemplary examples include one or more of graphite, graphene, and carbon nanotubes. Optionally, it may include one or more of Ag, Cu, C, Au, Al, ITO, AZO, BZO, or IZO, and more preferably one or more of Cu, Ag, and Au.

[0078] This application does not impose any particular limitation on the thickness of the second electrode 12; a thickness commonly used in the art for the second electrode 12 can be adopted. For example, the thickness of the second electrode 12 is 10 nm to 200 nm.

[0079] In other embodiments, other functional layers may also exist between the first light absorption layer 13 and the first and / or second electrode, including but not limited to, carrier transport layer, carrier blocking layer, passivation layer, etc.

[0080] In some embodiments, the solar cell further includes a first carrier transport layer disposed between the first electrode and the first light-absorbing layer; and / or a second carrier transport layer disposed between the first light-absorbing layer and the second electrode; wherein the first carrier transport layer is one of an electron transport layer (ETL) or a hole transport layer (HTL); and the second carrier transport layer is the other of an electron transport layer or a hole transport layer. By providing the first carrier transport layer and / or the second carrier transport layer, the extraction and transport of electrons and holes can be enhanced, thereby helping to improve the photoelectric conversion efficiency of the solar cell.

[0081] In this application, the solar cell may include both a first carrier transport layer and a second carrier transport layer, or it may include only one of the first carrier transport layer and the second carrier transport layer; there is no limitation herein. Optionally, the solar cell may include both a first carrier transport layer and a second carrier transport layer.

[0082] In this application, the electron transport layer has the function of transporting electrons, which is used to transport electrons generated by the excitation of the first light absorption layer 13 to the adjacent electrode and prevent electrons from diffusing in the opposite direction.

[0083] This application does not impose any particular limitation on the electron transport material used in the electron transport layer; commonly used electron transport materials in the art can be used. For example, electron transport materials include at least one of imide compounds, quinone compounds, fullerenes, metal oxides, semiconductor oxides, titanates, fluorides and their derivatives, and materials obtained by doping or passivation thereof. Exemplarily, imide compounds include at least one of phthalimide, succinimide, N-bromosuccinimide, glutarimide, or maleimide. Fullerenes and their derivatives include [6,6]-phenylC 61 Methyl butyrate (PC61BM), [6,6]-phenyl C 71 Methyl butyrate (PC71BM), Fullerene C 60 (C 60 ), fullerene C 70 (C 70 At least one of the following. For example, quinone compounds include at least one of benzoquinone, naphthoquinone, phenanthrenequinone, or anthraquinone. For example, the metal oxide includes at least one of Mg, Cd, Zn, In, Pb, W, Sb, Bi, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, and Cr. Optionally, the metal oxide includes at least one of tin dioxide (SnO2), zinc oxide (ZnO), and titanium dioxide (TiO2). For example, the semiconductor material oxide includes silicon oxide. For example, the titanate includes at least one of strontium titanate and calcium titanate. For example, the fluoride includes at least one of lithium fluoride and calcium fluoride.

[0084] This application does not impose any particular limitation on the thickness of the electron transport layer; any thickness conventionally used in the art for electron transport layers may be adopted. For example, the thickness of the electron transport layer is 5 nm to 100 nm.

[0085] In this application, the hole transport layer has the function of extracting and transporting holes, which is used to transport the holes generated by the excitation of the perovskite layer 13 to the adjacent electrode and prevent the holes from diffusing in the opposite direction.

[0086] This application does not impose any particular limitation on the hole transport material used in the hole transport layer; hole transport materials commonly used in the art can be used. Exemplary hole transport materials include poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), poly-3-hexylthiophene (P3HT), triphenylamine with a triphenylene core (H101), 3,4-ethylenedioxythiophene-methoxytriphenylamine (EDOT-OMeTPA), and N-(4-aniline)carbazole-spirobifluorene (C zPAF-SBF), a mixture of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT-PSS), polythiophene, phosphate monomers or polymers, carbazole monomers or polymers, sulfonic acid monomers or polymers, triphenylamine monomers or polymers, aromatic monomers or polymers, metal oxides, cuprous iodide, and cuprous thiocyanate, wherein the metal element in the metal oxide may include one or more of Ni, Mo, W, and Cu, such as nickel oxide (NiO). x ) and metal-doped nickel oxides (Li-doped NiO) x Mg-doped NiO x Cu-doped NiO x Sn-doped NiO x Zn-doped NiO x Sr-doped NiO x Co-doped NiO x ), WO3.

[0087] This application does not impose any particular limitation on the thickness of the hole transport layer; a thickness commonly used in the art for hole transport layers may be adopted. For example, the thickness of the hole transport layer is 1 nm to 200 nm.

[0088] Figure 2A schematic diagram of a solar cell according to an embodiment of this application is shown. In this embodiment, the solar cell 10 includes a first electrode 11, a hole transport layer 141, a first light absorption layer 13, an electron transport layer 142, and a second electrode 12 arranged sequentially along the direction of light incidence. In this embodiment, the first electrode 11, the hole transport layer 141, the first light absorption layer 13, the electron transport layer 142, and the second electrode 12 are as described above and will not be repeated here.

[0089] Those skilled in the art will understand that Figure 2 This is merely an illustrative example showing that the hole transport layer 141 is disposed on the side of the first light absorption layer 13 facing the first electrode 11, and the electron transport layer 142 is disposed on the side of the first light absorption layer 13 facing the second electrode 12. In some embodiments, the positions of the hole transport layer 141 and the electron transport layer 142 can be interchanged, that is, the electron transport layer 142 is disposed on the side of the first light absorption layer 13 facing the first electrode 11, and the hole transport layer 141 is disposed on the side of the first light absorption layer 13 facing the second electrode 12.

[0090] In some embodiments, the solar cell further includes a hole-blocking layer (not shown) located on the side of the electron transport layer 142 away from the first light-absorbing layer 13, for blocking the transmission of holes. By providing the hole-blocking layer, both electron extraction performance and hole blocking performance can be improved.

[0091] In some embodiments, the hole blocking layer includes a hole blocking material. This application does not have any particular limitation on the hole blocking material. For example, the hole blocking material may include one or more of SnO2 (1.5≤z≤2) and copper bath (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, BCP).

[0092] This application does not impose any particular limitation on the thickness of the hole blocking layer; a thickness commonly used in the art for hole blocking layers may be adopted. For example, the thickness of the hole blocking layer is 10 nm to 40 nm.

[0093] In some embodiments, the solar cell further includes a passivation layer (not shown) disposed on at least one surface of the first light-absorbing layer 13, thereby helping to reduce defects at the interface and further improve the performance of the solar cell. The passivation layer may include passivating agents conventionally used in the art for passivating the first light-absorbing layer, such as small organic molecules, organic salts, inorganic salts, polymers, etc. Small organic molecule passivating agents include, but are not limited to, phenylethylamine, ethylenediamine, pyridine, butanethiol, 2,5-thiophene dicarboxylic acid, etc. Organic salt passivating materials include, but are not limited to, piperazine iodine, phenylethylamine hydroiodate, dodecyl hydroiodate, guanidine bromide, thiophene ethylamine hydroiodate, ethylenediamine hydroiodate, and oleylamine iodine. Inorganic salt passivating materials include, but are not limited to, zinc chloride, potassium chloride, and gallium chloride. Polymer passivating materials include, but are not limited to, polymethyl methacrylate, polyethylene oxide, polyacrylonitrile, and polyvinyl alcohol.

[0094] In some embodiments, the solar cell further includes a substrate layer (not shown) disposed on the side of the first electrode 11 away from the first light-absorbing layer 13 for supporting the solar cell. The substrate layer can be, but is not limited to, a glass substrate or a flexible substrate. The material of the flexible substrate layer can be, for example (but not limited to), an organic polymer material, and further, can be one or more of the following materials mixed in different proportions: including but not limited to polyvinyl alcohol (PVA), polyester (PET), polyimide (PI), polyethylene naphthalate (PEN), polydimethylsiloxane (PDMS), etc.

[0095] In some embodiments, the solar cell further includes a second light-absorbing layer disposed between the first electrode and the second electrode, the second light-absorbing layer having a different band gap than the first light-absorbing layer. Thus, by providing a first light-absorbing layer and a second light-absorbing layer with different band gaps, the solar cell can effectively absorb light of different wavelengths, broadening the spectral range of absorbed light and improving the photoelectric conversion efficiency of the solar cell; thus, this solar cell is a tandem solar cell. In some embodiments, the second light-absorbing layer is located on the side of the first light-absorbing layer facing the first electrode. In other embodiments, the second light-absorbing layer is located on the side of the first light-absorbing layer facing the second electrode.

[0096] Figure 3 A schematic diagram of the structure of a solar cell according to another embodiment of this application is shown. The solar cell includes a first electrode 11, a first light-absorbing layer 13, a second light-absorbing layer 15, and a second electrode 12, which are stacked sequentially.

[0097] In some embodiments, the second light-absorbing layer comprises a layer of compounds such as a second perovskite material, crystalline silicon, copper zinc tin sulfide, copper zinc tin selenide, copper zinc tin selenide sulfide, copper indium gallium selenide, copper indium gallium diselenide, or copper indium selenide. These materials can absorb light of different wavelengths than the first light-absorbing layer, thereby broadening the spectral range of light absorbed by the solar cell and improving its photoelectric conversion efficiency.

[0098] In this application, the second perovskite material is different from the first perovskite material mentioned above. The second perovskite material includes at least one of the compounds shown in [A'][B'][X']3 and [A']2[C][D][X']6, wherein A' includes at least one of inorganic or organic monovalent cations, B' includes at least one inorganic divalent cation, C includes at least one inorganic monovalent cation, D includes at least one inorganic trivalent cation, and X' includes at least one monovalent anion.

[0099] For example, organic monovalent cations include (NR4R5R6R7). + (R4R5N=CR6R7) + (R4R5N-C(R8)=NR6R7) + Or (R4R5N-C(NR8R9)=NR6R7) + One or more of the following, wherein R4, R5, R6, R7, R8, and R9 are each independently selected from H, substituted or unsubstituted C1-C20 alkyl groups, or substituted or unsubstituted aryl groups. Optionally, the organic monovalent cation includes (H2N=CH-NH2). + (abbreviated as FA), CH3NH3 + One or more of (abbreviated as MA).

[0100] For example, the inorganic monovalent cation includes: Li + Na + K + 、Rb + Cs + Cu + Ag + Au + or Hg + At least one of them.

[0101] For example, the inorganic divalent cation includes: Pb 2+ Sn 2+ Be 2+ Mg 2+ Ca 2+ 、Sr 2+ Ba 2+ Zn 2+ 、Ge2+ Fe 2+ Co 2+ Ni 2+ Cd 2+ Cu 2+ Mn 2+ Pd 2+ Yb 2+ Or Eu 2+ At least one of them.

[0102] For example, inorganic trivalent cations include: Bi 3+ Sb 3+ Cr 3+ Fe 3+ Co 3+ Ga 3+ As 3+ Ru 3+ ,Rh 3+ In 3+ Ir 3+ Au 3+ Or Al 3+ At least one of them.

[0103] For example, monovalent anions include: F - Cl - ,Br - I - SCN - CNO - OCN - OSCN - SH - OH - CN - SeCN - At least one of them.

[0104] In some embodiments, the band gap of the second light-absorbing layer is 1.65 eV to 2.2 eV, or 1.1 eV to 1.2 eV. Thus, the band gap configuration of the first and second light-absorbing layers can effectively absorb both short-wavelength and long-wavelength light, improving the photoelectric conversion efficiency of the solar cell.

[0105] In some embodiments, a solar cell includes a first electrode, an optional first carrier transport layer, a first light-absorbing layer, an optional second carrier transport layer, a composite layer, an optional third carrier transport layer, a second light-absorbing layer, an optional fourth carrier transport layer, and a second electrode, all stacked together. The first carrier transport layer is selected from either a hole transport layer or an electron transport layer; the second carrier transport layer is selected from either a hole transport layer or an electron transport layer; the third carrier transport layer has the same carrier transport performance as the first carrier transport layer; and the fourth carrier transport layer has the same carrier transport performance as the second carrier transport layer. Thus, the arrangement of the carrier transport layers facilitates the extraction and transport of electrons or holes generated by the first or second light-absorbing layer, enhancing the extraction and transport effect of electrons and holes and improving the performance of the solar cell.

[0106] In this application, the solar cell may simultaneously include a first carrier transport layer, a second carrier transport layer, a third carrier transport layer, and a fourth carrier transport layer, or it may include only one or more of the first, second, third, and fourth carrier transport layers; no limitation is made here. The definition and material selection of the hole transport layer or electron transport layer are as described above.

[0107] In the case of simultaneously containing four types of charge carrier transport layers, the first electrode, the first charge carrier transport layer, the first light absorption layer, and the second charge carrier transport layer constitute the first battery section, and the third charge carrier transport layer, the second light absorption layer, the fourth charge carrier transport layer, and the second electrode constitute the second battery section. The composite layer is used to recombine and annihilate opposite charge carriers transported from the first light absorption layer and the second light absorption layer toward the composite layer to achieve low-ohmic tunnel recombination between the first battery section containing the first light absorption layer and the second battery section containing the second light absorption layer. For example, the components of the composite layer include one or more of metallic materials, transparent conductive oxides, and carbon materials. Further, the components of the transparent conductive oxide layer include, but are not limited to, one or more of FTO (fluorine-doped tin oxide), ITO (indium tin oxide), AZO (aluminum-doped zinc oxide), BZO (boron-doped zinc oxide), IZO (indium zinc oxide), IGZO (indium gallium zinc oxide), and ATO (antimony tin oxide). Further, the metallic materials include, but are not limited to, one or more of gold, copper, silver, platinum, aluminum, and iron. Furthermore, carbon materials include one or more of graphite, graphene, and carbon nanotubes.

[0108] In some embodiments, the thickness of the composite layer is 0.1 nm to 200 nm. For example, it can be 0.1 nm, 0.8 nm, 1 nm, 2 nm, 10 nm, 30 nm, 50 nm, 90 nm, 100 nm, 130 nm, 150 nm, 160 nm, 200 nm, or within the range of any two of the above point values ​​as end values.

[0109] Multijunction solar cells

[0110] A second aspect of this application provides a multi-junction solar cell, comprising a first sub-cell disposed on one side of the second sub-cell along its thickness direction, wherein the first sub-cell is the solar cell described in the first aspect of this application. Thus, the superposition of the two sub-cells allows for the absorption of more light to generate more electron-hole pairs, thereby improving the photoelectric conversion performance of the solar cell.

[0111] Figure 4 A schematic diagram of a multi-junction solar cell according to an embodiment of this application is shown. In this embodiment, the multi-junction solar cell 200 includes a first sub-cell 201 and a second sub-cell 202 arranged sequentially along the direction of light incidence. In this embodiment, the first sub-cell is a solar cell as described above, and will not be repeated here.

[0112] In some embodiments, the second sub-cell includes at least a third light-absorbing layer, which may be a third perovskite material, crystalline silicon, copper zinc tin sulfide, copper zinc tin selenide, copper zinc tin selenide sulfide, copper indium gallium selenide, copper indium gallium diselenide, or copper indium selenide. These materials can absorb light of different wavelengths than the first light-absorbing layer, thereby broadening the spectral range of light absorption in the solar cell and improving its photoelectric conversion efficiency.

[0113] In this application, the definition of the third perovskite material is the same as that of the second perovskite material, and will not be repeated here.

[0114] A multi-junction solar cell includes a first electrode, an optional first carrier transport layer, a first light absorption layer, an optional second carrier transport layer, a third electrode, an insulating layer, a fourth electrode, an optional fifth carrier transport layer, a third light absorption layer, an optional sixth carrier transport layer, and a second electrode, all stacked together. The first carrier transport layer is selected from either a hole transport layer or an electron transport layer; the second carrier transport layer is selected from either a hole transport layer or an electron transport layer; the fifth carrier transport layer is selected from either a hole transport layer or an electron transport layer; and the sixth carrier transport layer is selected from either a hole transport layer or an electron transport layer. Thus, the first electrode, a optional first carrier transport layer, a first light absorption layer, a optional second carrier transport layer, and the third electrode form the first sub-cell; the fourth electrode, a optional fifth carrier transport layer, the third light absorption layer, a optional sixth carrier transport layer, and the second electrode form the second sub-cell. The first and second sub-cells are isolated in the circuit by an insulating layer. Each cell has two electrodes, for a total of four electrodes. The circuits of the two sub-cells are independent of each other, forming a four-terminal multi-junction solar cell. Therefore, the current of the multi-junction solar cell can be adjusted.

[0115] In some implementations, the first carrier transport layer may have the same or different carrier transport performance as the fifth carrier transport layer, the insulating layer separates the two battery sections, and the current directions of the two sub-cells may be the same or different.

[0116] Furthermore, since the third and fourth electrodes are located in the middle of the multi-junction solar cell, in order to further increase the light energy utilization of the multi-junction solar cell and allow the remaining light after absorption by one sub-cell to enter the next sub-cell, the third and fourth electrodes can be set as light-transmitting electrodes. In some embodiments, the material of the insulating layer includes, but is not limited to, glass or an insulating adhesive. Further, the glass is transparent glass; further, the insulating adhesive is a transparent adhesive.

[0117] Methods for preparing solar cells

[0118] A third aspect of this application provides a method for fabricating a solar cell, comprising forming a first light-absorbing layer, wherein forming the first light-absorbing layer includes the following steps:

[0119] Preparation of perovskite precursor solution: Dissolve metal iodide, (H2N-CH=NH2)I, first additive and second additive in solvent and stir to obtain perovskite precursor solution. Metal iodide includes one or both of PbI2 or SnI2. The first additive and second additive together form a volatile compound.

[0120] Preparation of the first light-absorbing layer: The perovskite precursor solution is coated on the substrate and heat-treated to form the first light-absorbing layer.

[0121] In this application, the term "volatile compound" refers to a compound that is readily removed by evaporation or decomposition. For example, a compound that is readily removed by evaporation or decomposition at a temperature of 150°C or less, or for example, at a temperature of 100°C or less, is a volatile compound. "Volatile compound" also includes compounds that are readily removed by evaporating their decomposition products. Therefore, volatile compound X can be readily evaporated by evaporating the molecules of X, or volatile compound X can be readily evaporated by decomposing to form two readily evaporable compounds Y and Z.

[0122] In this application, the first additive and the second additive interact with metal iodides or ions generated by the ionization of (H2N-CH=NH2)I in the perovskite precursor solution, thereby inducing (H2N-CH=NH2) through molecular forces. +The crystals are aligned towards the (111) crystal plane to release crystal stress, which is beneficial for the prepared modified perovskite material to have good stability at room temperature. Furthermore, during the subsequent heat treatment process, the first additive and the second additive together form volatile compounds that can be removed from the first light absorption layer and will not enter the crystal structure of the first perovskite material. This is beneficial for preparing a stable active phase first perovskite material. Since no other ions are doped into the perovskite crystal lattice, the band gap of the prepared first perovskite material changes little compared to the reference band gap. The difference between the band gap of the first perovskite material and the reference band gap is less than or equal to 0.05 eV.

[0123] In some embodiments, during the step of preparing the perovskite precursor solution, the molar percentage of the first additive or the second additive relative to the molar amount of the metal iodide is 1 mol% to 10 mol%. This helps to reduce the residual amount of the first additive, the second additive, and their reaction products in the subsequently prepared perovskite layer, improves the purity of the modified perovskite material, and thus improves the photoelectric conversion efficiency of the solar cell. Exemplarily, during the step of preparing the perovskite precursor solution, the molar percentage of the first additive or the second additive relative to the molar amount of the metal iodide can be 1 mol%, 2 mol%, 4 mol%, 5 mol%, 8 mol%, 10 mol%, or a value within a range of any two of these values. In some optional embodiments, during the step of preparing the perovskite precursor solution, the molar percentage of the first additive or the second additive relative to the molar amount of the metal iodide is 5 mol% to 10 mol%. This further helps to improve the stability of the prepared first perovskite material, reduces the difference between its band gap and the reference band gap, and thus helps to improve the efficiency of the solar cell.

[0124] In some embodiments, the first additive is R1-CO-NH2, and the second additive is an organic amine salt, wherein the organic amine salt corresponds to an organic amine with the structural formula R2-NH-R3, where R1 is selected from H, C1-C3 alkyl, and R2 and R3 are each independently selected from H, branched or straight-chain C1-C4 alkyl, and R2 and R3 are not both hydrogen. By adding the first and second additives to the precursor solution, the ion formed by the disubstituted amine salt can react with (H2N-CH=NH2). + It forms a chelating agent, which induces molecular forces (H2N-CH=NH2) during the formation of perovskite crystals. +The crystals are aligned towards the (111) crystal plane to release crystal stress, which is beneficial to the good stability of the prepared first perovskite material at room temperature. Furthermore, in the subsequent heat treatment process, the first additive and the second additive react according to the following reaction equation, wherein the boiling point of the generated DEF substance is less than or equal to the boiling point of the solvent, for example, less than or equal to 200°C. Thus, during the heat treatment process, the reaction products of the first and second additives are volatilized by heat and will not enter the crystal structure of the modified perovskite material. This is beneficial to the preparation of a stable active phase modified perovskite material. Moreover, since no other ion dopants enter the perovskite lattice, the band gap of the prepared modified perovskite material changes little compared to the reference band gap. The difference between the band gap of the modified perovskite material and the reference band gap is less than or equal to 0.05 eV.

[0125]

[0126] In this application, R1 is selected from H and C1-C3 alkyl groups, and R2 and R3 are each independently selected from H, branched or straight-chain C1-C4 alkyl groups, and R2 and R3 are not both hydrogen. This is advantageous because the reaction products of the first and second additives have low boiling points, for example, less than or equal to 200°C, which facilitates removal from the perovskite layer during heat treatment and prevents them from entering the lattice of the modified perovskite material, thereby helping to reduce the difference between the band gap of the modified perovskite material and the reference band gap.

[0127] In this application, the term "alkyl" refers to an alkyl group having the general formula C2. n H 2n+1 A monovalent group is a group formed by removing one hydrogen atom from a saturated, straight-chain or branched aliphatic hydrocarbon. C1-Cn alkyl refers to a straight-chain or branched alkyl group having 1 to n carbon atoms. Examples of C1-C4 alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, etc.

[0128] In some embodiments, the first additive is selected from one or more of formamide, acetamide, propionamide, and 2-methylpropionamide.

[0129] In some embodiments, the salt corresponding to the organic amine salt is selected from one or more of hydrochloride, bromate, iodate, acetate, and sulfate.

[0130] In some embodiments, the organic amine salt corresponding to the cation is selected from one or more of dimethylamine cation, diethylamine cation, di-n-propylamine cation, diisopropylamine cation, di-n-butylamine cation, and diisobutylamine cation.

[0131] In some embodiments, the first and second additives comprise at least one of the following combinations: diethylamine hydrochloride and formamide, dimethylamine hydrochloride and formamide, di-n-propylamine hydrochloride and formamide, di-n-butylamine hydrochloride and formamide, diethylamine hydrochloride and acetamide, and diethylamine hydrochloride and propionamide. This further improves the stability of the prepared modified perovskite material, reduces the difference between the band gap and the reference band gap, and thus improves the photoelectric conversion efficiency of the solar cell.

[0132] In some embodiments, the molar ratio of the first additive to the second additive is 1 to 1.2:1. This facilitates the full reaction of the first additive, allowing the reaction products and remaining reactants to be removed from the perovskite layer during heat treatment. This helps reduce or even eliminate the influence of impurities on the band gap and stability of the perovskite material, resulting in a perovskite material with a band gap closer to the reference band gap, thereby improving the performance of the solar cell. Exemplarily, the molar ratio of the first additive to the second additive can be 1:1.05, 1:1.1, 1:1.15, 1:2, or a value within a range of any two of these values.

[0133] In some embodiments, the molar concentrations of metal iodide and (H₂N-CH=NH₂)I in the perovskite precursor solution are each independently 1-2 mol / L. Maintaining the molar concentrations of metal iodide and (H₂N-CH=NH₂)I within this range is beneficial for improving the crystallinity of the first perovskite material, thereby enhancing the performance of the perovskite solar cell. Exemplarily, the molar concentrations of metal iodide and (H₂N-CH=NH₂)I in the perovskite precursor solution are each independently 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, or a range consisting of any two of these values. In some alternative embodiments, the molar concentrations of metal iodide and (H₂N-CH=NH₂)I are each independently 1.4-1.6 mol / L. In some alternative embodiments, the molar concentrations of metal iodide and (H₂N-CH=NH₂)I are the same. This helps improve the crystal quality of the first perovskite material, thereby enhancing the performance of perovskite solar cells, and also saves on raw material costs.

[0134] In this application, the solvent is used to dissolve the perovskite precursor raw material, the first additive, and the second additive. This application does not impose any particular limitation on the solvent, as long as it can dissolve the perovskite precursor raw material, the first additive, and the second additive. In some embodiments, the solvent includes dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1 to 6:1. Exemplarily, the volume ratio of dimethylformamide to dimethyl sulfoxide in the solvent is 3:1, 4:1, 5:1, 5.5:1, 6:1, or a value within a range consisting of any two of these values. In some embodiments, the solvent includes N-methylpyrrolidone and dimethyl sulfoxide in a volume ratio of 3:1 to 6:1.

[0135] In this application, the purpose of stirring in the step of preparing the perovskite precursor solution is to ensure that all reactants are thoroughly mixed and uniformly dispersed. This application does not specify the method, apparatus, or stirring time for stirring, as long as the goal of uniformly dispersing the reactants is achieved. In some embodiments, stirring includes stirring overnight under a protective atmosphere.

[0136] This application does not impose any particular limitation on the coating method of the perovskite precursor solution. For example, the perovskite precursor solution can be coated by spin coating, slot coating, or blade coating.

[0137] In some embodiments, the substrate may be an electrode, a carrier transport layer, or other functional layers stacked in contact with the first light-absorbing layer. This application does not limit the specific substrate.

[0138] In some embodiments, the coating process in the step of preparing the first light-absorbing layer includes spin-coating a perovskite precursor solution onto the hole transport layer and drying it using an air knife to form a film.

[0139] In this application, the purpose of air knife purging is to accelerate the solvent evaporation of the perovskite precursor solution and form a homogeneous perovskite mesophase. This application does not specify the equipment and parameters for air knife purging.

[0140] In some embodiments, the heat treatment in the step of preparing the first light-absorbing layer includes annealing at 80-120°C for 8-20 minutes. This facilitates the formation of a stable perovskite crystal phase, improves the stability of the first perovskite material, and thus enhances the performance of the solar cell.

[0141] The fabrication methods for the other functional layers of a solar cell (first electrode, second electrode, carrier transport layer, carrier blocking layer, passivation layer, etc.) are not particularly limited and can include fabrication methods conventional in the art. Examples include spin coating, spray coating, slot coating, chemical bath deposition, electrochemical deposition, chemical vapor deposition, physical epitaxial growth, vacuum thermal evaporation, atomic layer deposition, magnetron sputtering, and mechanical pressing.

[0142] This application also provides a photovoltaic module, including the solar cell or multi-junction solar cell provided in the above embodiments. In some embodiments, the photovoltaic module further includes solder strips connecting multiple solar cells, a junction box for current transmission, and a cell encapsulation component.

[0143] In some embodiments, the battery encapsulation component includes photovoltaic glass. The photovoltaic glass covers the aforementioned solar cell, serving to protect it. Simultaneously, the photovoltaic glass possesses excellent light transmittance and high hardness, allowing it to withstand large diurnal temperature variations and harsh weather conditions.

[0144] In some embodiments, the battery encapsulation component includes an ethylene-vinyl acetate copolymer (EVA) film disposed between the photovoltaic glass and the solar cell for bonding the photovoltaic glass and the solar cell.

[0145] In some implementations, the battery encapsulation components include a photovoltaic backsheet. The photovoltaic backsheet serves to protect the solar cells.

[0146] Optionally, the photovoltaic backsheet material may include a polyvinyl fluoride composite film or a thermoplastic elastic material. The photovoltaic backsheet material possesses properties such as insulation, water resistance, and aging resistance.

[0147] In some implementations, the battery mounting components include a solar panel aluminum frame, made of aluminum alloy, which features high strength and corrosion resistance. It serves to support and protect the solar cells.

[0148] This application also provides a power generation device, including the solar cell provided in the above embodiments.

[0149] This application also provides an electrical device, including the solar cell or multi-junction solar cell provided in the above embodiments.

[0150] In some embodiments, the electrical device includes lighting equipment, energy storage equipment, etc., and the embodiments of this application include, but are not limited to, these. For example, the electrical device includes solar water heaters, solar street lights, solar photovoltaic generators, etc.

[0151] Example

[0152] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0153] Example 1

[0154] Step S1, Preparation of the first electrode: Fluorine-doped tin oxide (FTO) conductive glass (size 2cm*2cm, FTO thickness 550nm) was ultrasonically cleaned for 15 minutes each with diluted detergent, deionized water, acetone, ethanol and isopropanol, and then placed in a 70℃ drying oven for 120 minutes to remove residual organic impurities, resulting in a clean and dry substrate material. After that, it was treated with ultraviolet-ozone for 15 minutes and then transferred to a glove box filled with nitrogen to serve as the first electrode.

[0155] Step S2, forming a hole transport layer: Poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) is used as the hole transport material, dissolved in toluene to form a 2 mg / mL solution, coated on an FTO substrate, and then annealed on a heating stage at 100°C for 10 min to obtain a hole transport layer of about 15 nm.

[0156] Step S3, forming a perovskite layer

[0157] Step S3-1, preparing the perovskite precursor solution: PbI2, (H2N-CH=NH2)I (FAI), the first additive, and the second additive are dissolved in a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) with a volume ratio of 5.5:1. The mixture is stirred overnight in a glove box filled with nitrogen to prepare the perovskite precursor solution. The concentrations of PbI2 and FAI in the perovskite precursor solution are both 1.4 mol / L. The first additive includes 5 mol% formamide relative to the molar amount of PbI2, and the second additive includes 5 mol% diethylamine hydrochloride relative to the molar amount of PbI2.

[0158] Step S3-2, Preparation of perovskite layer: The above perovskite precursor solution is filtered with a polytetrafluoroethylene filter. The filtered solution is then coated onto the hole transport layer using a one-step spin coating method. The solvent in the perovskite precursor solution is removed by air knife purging. The spin-coated perovskite precursor film is transferred to a heating stage and annealed at 100°C for 10 minutes to obtain a crystallized FAPbI3 perovskite layer with a thickness of 650 nm.

[0159] Step S4, forming an electron transport layer: [6,6]-phenyl-C61-butyrate methyl ester (PCBM) is dissolved in chlorobenzene to obtain a 20 mg / mL solution, which is then coated onto the perovskite layer and annealed on a heating stage at 70°C for 10 minutes to obtain the desired electron transport layer with a thickness of 20 nm.

[0160] Step S5, forming the interface layer: 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) is dissolved in methanol to form a 0.5 mg / mL solution, which is then coated onto the electron transport layer. After completion, the substrate is placed on a heating stage at 70°C for annealing for 10 minutes to obtain the interface layer with a thickness of 3 nm.

[0161] Step S6, Preparation of the second electrode: Using a vacuum thermal evaporation coating apparatus, a 100nm thick copper electrode is deposited... The perovskite solar cell is obtained by depositing the aforementioned interface layer at a high speed.

[0162] Example 2

[0163] Perovskite solar cells were prepared using a method similar to that in Example 1, except that in step S3-1, the first additive was 5 mol% formamide and the second additive was 5 mol% dimethylamine hydrochloride relative to the molar amount of PbI2.

[0164] Example 3

[0165] Perovskite solar cells were prepared using a method similar to that in Example 1, except that in step S3-1, the first additive was 5 mol% formamide and the second additive was 5 mol% dipropylamine hydrochloride relative to the molar amount of PbI2.

[0166] Example 4

[0167] Perovskite solar cells were prepared using a method similar to that in Example 1, except that in step S3-1, the first additive was 5 mol% formamide and the second additive was 5 mol% dibutylamine hydrochloride relative to the molar amount of PbI2.

[0168] Example 5

[0169] Perovskite solar cells were prepared using a method similar to that in Example 1, except that in step S3-1, the first additive was 5 mol% acetamide and the second additive was 5 mol% diethylamine hydrochloride relative to the molar amount of PbI2.

[0170] Example 6

[0171] Perovskite solar cells were prepared using a method similar to that in Example 1, except that in step S3-1, the first additive was 5 mol% propionamide and the second additive was 5 mol% diethylamine hydrochloride relative to the molar amount of PbI2.

[0172] Example 7

[0173] Perovskite solar cells were prepared using a method similar to that in Example 1, except that step S3-1 involved dissolving SnI2, (H2N-CH=NH2)I (FAI), and the first and second additives in a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) at a volume ratio of 5.5:1, stirring overnight in a nitrogen-filled glove box to prepare a perovskite precursor solution. In the perovskite precursor solution, the concentrations of SnI2 and FAI were both 1.4 mol / L. The first additive was 5 mol% formamide and the second additive was 5 mol% diethylamine hydrochloride relative to the molar amount of SnI2.

[0174] Example 8

[0175] Perovskite solar cells were prepared using a method similar to that in Example 1, except that step S3-1 involved dissolving PbI2, SnI2, (H2N-CH=NH2)I (FAI), the first additive, and the second additive in a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) at a volume ratio of 5.5:1, stirring overnight in a nitrogen-filled glove box to prepare a perovskite precursor solution. In the perovskite precursor solution, PbI2 and SnI2 were each 0.7 mol / L, and the concentration of FAI was 1.4 mol / L. The first additive was 5 mol% formamide and the second additive was 5 mol% diethylamine hydrochloride relative to the molar amount of SnI2.

[0176] Comparative Example 1

[0177] Perovskite solar cells were prepared using a method similar to that in Example 7, except that the first and second additives were not added in step S3-1.

[0178] Comparative Example 2

[0179] Perovskite solar cells were prepared using a method similar to that in Example 8, except that the first and second additives were not added in step S3-1.

[0180] Comparative Example 3

[0181] Perovskite solar cells were prepared using a method similar to that in Example 1, except that step S3-1 included preparation according to Cs. 0.05 (FA 0.92MA 0.08 ) 0.95 Pb(I 0.92 Br 0.08 3. The molar ratio of the elements in the chemical formula is as follows: PbI2, FAI, PbBr2, methylamine hydrobromide (MABr), CsI and methylamine hydrochloride (MACl) (20 mol%) are dissolved in a mixed solvent of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) with a volume ratio of 5.5:1. The mixture is stirred overnight in a glove box filled with nitrogen to prepare a perovskite precursor solution, wherein the concentrations of PbI2 and FAI in the perovskite precursor solution are 1.4 mol / L.

[0182] Comparative Example 4

[0183] Perovskite films were prepared using a method similar to steps S1-S3 of Example 1, except that no first additive and second additive were added in steps S3-1.

[0184] Parameter testing of perovskite materials

[0185] (1) Test of the ratio of (111) crystal plane and (001) crystal plane

[0186] The perovskite solar cell was disassembled to obtain the perovskite material of the perovskite layer. The obtained perovskite material was subjected to X-ray diffraction (XRD) testing with the following parameters: scanning range 2θ of 0-70°, and scanning step size of 0.3°. The XRD pattern of the material was obtained.

[0187] (2) Residual stress testing

[0188] The perovskite solar cell was disassembled to separate the perovskite material of the perovskite layer. Grazing incidence X-ray diffraction was used to detect the residual stress of the perovskite material. By gradually twisting the incident angle from 0° to 45° and monitoring the characteristics of the (111) crystal plane characteristic peak of the perovskite material, the 2θ-sin(θ) ... 2 The linear curve between ψ and ψ is fitted to obtain the slope of the curve, which represents the residual stress of the perovskite material.

[0189]

[0190] In the formula, E is the perovskite modulus, v is the Poisson's ratio of the perovskite, and E and v are estimated to be 10 GPa and 0.3, respectively. θ0 is half of the scattering angle 2θ0, which corresponds to the diffraction peak of stress-free perovskite, and 2θ0 is 24.33°.

[0191] (3) Bandgap test

[0192] Perovskite solar cells were disassembled to separate the perovskite layer material. The perovskite material was then tested at room temperature in an inert N2 environment with humidity below 3% RH using an Edinburgh DS5 UV-Vis spectrophotometer. During the test, the monochromatic light wavelength was scanned within the range of 300-900 nm, with a test step size of 5 nm. The wavelength-absorption curve of the perovskite material was obtained, where the horizontal axis represents wavelength and the vertical axis represents absorption intensity. A tangent line was drawn to the absorption plateau in the wavelength-absorption curve (i.e., the location of the largest change in absorbance in the wavelength-absorption curve), and the value of the intersection point with the horizontal axis was recorded as the band-edge wavelength λ. g The band gap E of the material can be calculated using the following formula. g .

[0193] E g =hc / λ g In the formula, h is Planck's constant, c is the speed of light, and λg is the band-side wavelength.

[0194] Solar performance testing

[0195] (1) Photoelectric conversion efficiency

[0196] The photoelectric conversion efficiency was determined using the IV measurement method, and the specific steps are as follows:

[0197] a) Place the test fixture containing the sample cell (i.e. the solar cell prepared in Example 1 above) on the sample holder, so that it is located in the measurement plane, and ensure that the sample cell is located at the center of the emitted light spot of the solar simulator (or the normal of the photovoltaic cell is parallel to the center line of the emitted beam of the solar simulator light source).

[0198] b) The solar simulator from Guangyan was used for testing in accordance with the national standard IEC61215. Specifically, crystalline silicon solar cells were used to correct the light intensity to achieve a solar intensity of AM 1.5, at 100 mW / cm². 2 Under irradiance conditions, a mask is installed on the sample battery to be tested, and the temperature of the sample battery is controlled by a temperature monitoring device so that the temperature of the sample battery is maintained at (30±5℃) during the measurement process.

[0199] c) Set the scan direction, voltage range, scan interval voltage, and scan interval time. Specifically, the scan interval is 10mV, and the interval between two adjacent points is 100ms. Measure the forward and reverse scan current-voltage characteristics of the battery sample and record the short-circuit current J. sc Open circuit voltage V oc Maximum optical output current J mpp and maximum light output voltage V mpp .

[0200] Next, the photoelectric conversion efficiency is calculated using the following formula:

[0201] Photoelectric conversion efficiency PCE = J sc ×V oc ×FF / Pw;

[0202] Fill factor FF = J sc ×V oc / (J mpp ×V mpp );

[0203] Among them, P w FF is the input power, and FF is the fill factor.

[0204] (2) Wet stability test

[0205] Humidity stability test: The sample battery was placed at room temperature (23±4℃), humidity of 50%RH, and under nitrogen protection. The device performance was tested once every 24 hours, and the time corresponding to when the photoelectric conversion efficiency of the battery decreased to 90% of the initial photoelectric conversion efficiency was recorded.

[0206] (3) Job stability

[0207] The sample was placed in a nitrogen atmosphere at 23±4℃ and continuously irradiated (1 sun). Maximum power point tracking (MPPT) was continuously performed during the irradiation process, and the JV curve was tested every 24 hours. The values ​​from each test were recorded, along with the time elapsed until the energy conversion efficiency consistently fell below 90% (T90). A longer T90 indicates a more stable battery.

[0208] The perovskite materials of Example 1 and Comparative Example 4 were subjected to XRD tests according to the above method. The test results are shown below. Figure 5 .from Figure 5 As can be seen, in the XRD pattern of Example 1, the diffraction peak intensity of the (111) crystal plane is significantly higher than that of the (001) crystal plane, indicating that the (111) crystal plane is the dominant crystal plane of the perovskite material prepared in Example 1. In contrast, the (001) crystal plane of the perovskite material in Comparative Example 4 has the highest diffraction peak intensity.

[0209] The residual stress in the lattice of the perovskite material from Example 1 was analyzed using the method described above. The test results are shown below. Figure 6 .Depend on Figure 6 It can be seen that the residual stress of the perovskite corresponding to Example 1 is 3.02 MPa. Compared with the residual stress of the multi-component perovskite prepared in Comparative Example 3 and the uncontrolled FAPbI3 perovskite in Comparative Example 4, the residual stress of the perovskite material in Example 1 of this application is significantly reduced, which is beneficial to enhancing the crystal structure stability of the perovskite material and thus improving the environmental stability and working stability of the perovskite solar cell.

[0210] The solar cells prepared in Examples 1-8 and Comparative Examples 1-3 were subjected to parameter testing of perovskite materials and performance testing of solar cells according to the above test methods. The test results are shown in Table 1.

[0211] Table 1

[0212]

[0213]

[0214]

[0215] Note: In the table, " / " indicates that no data was added, and "-" indicates that no data was measured.

[0216] The results above show that, compared to Comparative Examples 3-4, the (111) crystal plane accounts for more than 95% of the perovskite materials in Examples 1-6, and the residual stress in the perovskite lattice is less than 4 MPa. This indicates that the perovskite materials in Examples 1-6 have low residual stress in their crystal structure and good structural stability. Furthermore, the difference between the band gap and the reference band gap (1.47 eV for FAPbI3) of the perovskite materials in Examples 1-6 is less than 0.05 eV. This is beneficial for improving the photoelectric conversion efficiency of solar cells and provides good environmental and operational stability. Compared to Comparative Example 1, the (111) crystal plane is the dominant crystal plane in the perovskite material of Example 7, and the difference between the perovskite material of Example 7 and its reference band gap (1.33 eV for FASnI3) is even smaller. This is beneficial for the perovskite solar cells of Example 7 to have better photoelectric conversion efficiency and stability. Compared to Comparative Example 2, in the perovskite material of Example 8, the (111) crystal plane is the dominant crystal plane, and the band gap of the perovskite material of Example 8 is closer to the reference band gap (FAPb). 0.5 Sn 0.5 The reference bandgap of I3 is 1.21 eV, thus the solar cell of Example 8 has better photoelectric conversion efficiency and stability.

[0217] The perovskite films prepared in steps S1 to S3 of Example 1 were placed in an air environment with 50% RH and room temperature. The time it took for the perovskite films to retain 90% of their initial characteristic absorption intensity was tested. The results showed that this time exceeded 1000 hours, while the perovskite film in Comparative Example 4 retained 90% of its initial characteristic absorption intensity for less than 10 hours. The method for testing the characteristic absorption intensity is as follows: the absorption curve of the perovskite film was tested using a UV-Vis spectrophotometer. For Example 1 and Comparative Example 4, the absorption intensity at 832 nm of the fresh sample was defined as the characteristic absorption intensity (1240 / 1.49 nm, i.e., the wavelength corresponding to the band gap), and normalized. The retention rate of the characteristic absorption intensity was continuously monitored as humidity aging progressed, thereby obtaining the time it took for the perovskite film to retain 90% of its initial characteristic absorption intensity.

[0218] Examples 9-11

[0219] Examples 9-11 were prepared using a method similar to that of Example 1, except that in step S3-1, the amount of additives added was adjusted according to the composition of the additive pairs shown in Table 2.

[0220] The solar cells prepared in Examples 9-11 were tested according to the above test methods, and the test results are shown in Table 2.

[0221] Table 2

[0222]

[0223] As can be seen from the above results, during the preparation of the perovskite layer, by adjusting the molar concentration of the additive pair in Examples 9-11 to within the range of 1 mol%-10 mol% of the molar amount of PbI2, the perovskite material prepared has (111) crystal plane as the dominant crystal plane, and the difference between the band gap and the reference band gap is less than or equal to 0.05 eV. As a result, the perovskite solar cell has good photoelectric conversion efficiency, as well as good environmental stability and working stability.

[0224] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A solar cell, characterized in that, The solar cell includes a first light-absorbing layer. The first light-absorbing layer comprises a first perovskite material, which comprises a compound of formula (1). [A][B][X]3(1); In the formula, A is (H2N-CH=NH2). + B is selected from Pb 2+ Sn 2+ One or more of them; X is I - ; In the X-ray diffraction pattern of the compound of formula (1), the peak area of ​​the (111) crystal plane accounts for 80% to 100% of the sum of the peak areas of the (111) and (001) crystal planes. The difference between the band gap of the compound of formula (1) and the reference band gap is less than or equal to 0.05 eV, wherein the reference band gap is the band gap of the uncontrolled [A][B][X]3 perovskite in a stable cubic crystal phase measured by ultraviolet-visible spectroscopy.

2. The solar cell according to claim 1, characterized in that, In the X-ray diffraction pattern of the compound of formula (1), the peak area of ​​the (111) crystal plane accounts for 95%-97% of the sum of the peak areas of the (111) crystal plane and the (001) crystal plane.

3. The solar cell according to claim 1 or 2, characterized in that, The crystal structure of the compound of formula (1) belongs to the cubic crystal system, wherein the residual lattice stress of the compound of formula (1) is 0.1MPa-4.0MPa.

4. The solar cell according to any one of claims 1 to 3, characterized in that, The first light-absorbing layer also includes the compound shown in formula (2). In the formula, R1 is selected from H and C1-C3 alkyl groups, and R2 and R3 are each independently selected from H, branched or straight-chain C1-C4 alkyl groups, and R2 and R3 are not both hydrogen. The compound represented by formula (2) is located in the grain boundaries of the first perovskite material.

5. The solar cell according to any one of claims 4, characterized in that, The content of the compound represented by formula (2) is 0.01% to 0.5% relative to the total mass of the first light-absorbing layer.

6. The solar cell according to any one of claims 1 to 5, characterized in that, The solar cell further includes a first electrode and a second electrode, wherein the first light-absorbing layer is disposed between the first electrode and the second electrode.

7. The solar cell according to claim 6, characterized in that, The solar cell further includes a first carrier transport layer disposed between the first electrode and the first light absorption layer, and / or a second carrier transport layer disposed between the second electrode and the first light absorption layer; wherein the first carrier transport layer is selected from one of a hole transport layer or an electron transport layer, and the second carrier transport layer is selected from the other of a hole transport layer or an electron transport layer.

8. The solar cell according to claim 6 or 7, characterized in that, The solar cell further includes a second light-absorbing layer disposed between the first electrode and the second electrode, wherein the band gap of the first light-absorbing layer is different from that of the second light-absorbing layer.

9. The solar cell according to claim 8, characterized in that, The second light-absorbing layer comprises a layer of the following compounds: a second perovskite material, crystalline silicon, copper zinc tin sulfide, copper zinc tin selenide, copper zinc tin selenide sulfide, copper indium gallium selenide, copper indium gallium diselenide, or copper indium selenide.

10. The solar cell according to claim 8 or 9, characterized in that, The solar cell includes a first electrode, an optional first carrier transport layer, a first light absorption layer, an optional second carrier transport layer, a composite layer, an optional third carrier transport layer, the second light absorption layer, an optional fourth carrier transport layer, and a second electrode, all stacked together. The first carrier transport layer is selected from either a hole transport layer or an electron transport layer, the second carrier transport layer is selected from either a hole transport layer or an electron transport layer, the third carrier transport layer has the same carrier transport performance as the first carrier transport layer, and the fourth carrier transport layer has the same carrier transport performance as the second carrier transport layer.

11. A multi-junction solar cell, characterized in that, A first sub-cell is disposed on one side of the second sub-cell along the thickness direction, wherein the first sub-cell is a solar cell according to any one of claims 1 to 10.

12. The multi-junction solar cell according to claim 11, characterized in that, The second sub-cell includes at least a third light-absorbing layer, which includes a third perovskite material, crystalline silicon, copper zinc tin sulfide, copper zinc tin selenide, copper zinc tin selenide sulfide, copper indium gallium selenide, copper indium gallium diselenide, or copper indium selenide.

13. The multi-junction solar cell according to claim 11 or 12, characterized in that, The multi-junction solar cell includes a first electrode, an optional first carrier transport layer, a first light absorption layer, an optional second carrier transport layer, a third electrode, an insulating layer, a fourth electrode, an optional fifth carrier transport layer, the third light absorption layer, an optional sixth carrier transport layer, and a second electrode, all stacked together. The first carrier transport layer is selected from either a hole transport layer or an electron transport layer; the second carrier transport layer is selected from either a hole transport layer or an electron transport layer; the fifth carrier transport layer is selected from either a hole transport layer or an electron transport layer; and the sixth carrier transport layer is selected from either a hole transport layer or an electron transport layer.

14. A method for preparing a solar cell, characterized in that, This includes forming a first light-absorbing layer, wherein forming the first light-absorbing layer includes the following steps: Preparation of perovskite precursor solution: Dissolve metal iodide, (H2N-CH=NH2)I, first additive and second additive in solvent and stir to obtain perovskite precursor solution. The metal iodide includes one or both of PbI2 or SnI2. The first additive and second additive together form a volatile compound. Preparation of the first light-absorbing layer: The perovskite precursor solution is coated on the substrate and heat-treated to form the first light-absorbing layer.

15. The preparation method according to claim 14, characterized in that, In the step of preparing the perovskite precursor solution, the molar percentage of the first additive or the second additive is 1 mol% to 10 mol% relative to the molar amount of the metal iodide.

16. The preparation method according to claim 14 or 15, characterized in that, The first additive is R1-CO-NH2, and the second additive is an organic amine salt, wherein the organic amine salt corresponds to an organic amine with the structural formula R2-NH-R3, where R1 is selected from H or C1-C3 alkyl, and R2 and R3 are each independently selected from H, branched or straight-chain C1-C4 alkyl, and R2 and R3 are not both hydrogen.

17. The preparation method according to claim 16, characterized in that, The preparation method satisfies one or more of the following conditions: (1) The first additive is selected from one or more of formamide, acetamide, propionamide, and 2-methylpropionamide; (2) The salt corresponding to the organic amine salt is selected from one or more of hydrochloride, bromate, iodate, acetate, and sulfate; (3) The organic amine salt corresponding to the cation is selected from one or more of dimethylamine cation, diethylamine cation, di-n-propylamine cation, diisopropylamine cation, di-n-butylamine cation, and diisobutylamine cation.

18. The preparation method according to any one of claims 14 to 17, characterized in that, The molar ratio of the first additive to the second additive is 1 to 1.2:

1.

19. The preparation method according to any one of claims 14 to 18, characterized in that, In the perovskite precursor solution, the molar concentrations of the metal iodide and (H2N-CH=NH2)I are each 1-2 mol / L independently.

20. The preparation method according to any one of claims 14 to 19, characterized in that, In the step of preparing the perovskite layer, the heat treatment includes annealing at 80-120°C for 8-20 minutes.

21. A photovoltaic module, characterized in that, The photovoltaic module includes the solar cell according to any one of claims 1 to 10, the multi-junction solar cell according to any one of claims 11 to 13, or the solar cell prepared by the method according to any one of claims 14 to 20.

22. A power generation device, characterized in that, The power generation device includes a solar cell according to any one of claims 1 to 10, a multi-junction solar cell according to any one of claims 11 to 13, or a solar cell prepared by any one of claims 14 to 20.

23. An electrical appliance, characterized in that, The electrical device includes a solar cell according to any one of claims 1 to 10, a multi-junction solar cell according to any one of claims 11 to 13, or a solar cell prepared by any one of claims 14 to 20.